PC / ABS material with high paint spraying yield, and preparation method and application thereof

CN121699358BActive Publication Date: 2026-10-27SHANGHAI KUMHO SUNNY PLASTICS +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511943098.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-10-27
Estimated Expiration
2045-12-22

AI Technical Summary

Technical Problem

例如,在中国专利CN111040406B,所公开的一种高耐热、耐化学品性ABS/PC合金,利用PBT分子链段运动快,易迁移到制件表面形成保护层的特性提高ABS/PC合金的耐化学性能,但是由于PBT的与PC的酯交换和水解反应,实际使用中形成的保护层的效率较低,因此需要添加较多的PBT才能达到理想的效果

Benefits of technology

(1)本发明PC/ABS材料具有优异的机械性能、耐热性能和耐化学性能,在喷漆后尺寸稳定,耐喷漆腐蚀,不易发生开裂,适用于汽车高长宽比的外饰制件及其他室外场景使用的喷漆制件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application relates to a PC / ABS material with a high paint spraying yield and a preparation method and application thereof, and the material comprises the following components in parts by weight: PC resin 45-80 parts; ABS resin 20-30 parts; PBT resin 5-15 parts; toughening agent 1-5 parts; PBT protective master batch 2-10 parts. Compared with the prior art, the PC / ABS alloy material prepared by the application has an excellent paint spraying yield and is suitable for the forming injection of automobile spoiler and other high length-width ratio products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a PC / ABS material with high paint yield, its preparation method, and its application. Background Technology

[0002] In recent years, the technology and market for new energy vehicles have developed rapidly. Compared to traditional gasoline vehicles, new energy vehicles place greater emphasis on appearance and technological sophistication. Features such as multi-screen displays, variable rear wings, and lidar are increasingly becoming standard equipment in new energy vehicles. These newly added parts share a common characteristic: they are relatively large, especially exterior parts such as rear wings, which are directly exposed to the natural environment. To ensure normal operation under extreme weather conditions such as high temperature and humidity, the mechanical properties, lightweight properties, and thermal stability of the materials are often very high. Plastics have a low specific gravity and, after modification, possess excellent weather resistance, low-temperature resistance, and aging resistance. Therefore, modified plastics account for a high proportion of automotive interior and exterior trim.

[0003] PC / ABS alloys combine the excellent mechanical properties and heat resistance of polycarbonate (PC) with the good processability and impact resistance of acrylonitrile-butadiene-styrene copolymer (ABS). It is one of the world's best-selling commercial polymer alloys, with demand growing at a rate of nearly 10% annually in recent years, particularly in the automotive and electronics industries where high heat resistance and toughness are required. It is the preferred choice for components such as automotive spoilers. However, PC / ABS still has the disadvantage of poor UV resistance, and when used in automotive exteriors, surface treatment is usually required, with painting being the most common post-processing technique.

[0004] While PC alloys possess excellent mechanical and heat resistance properties, their narrow processing window during the machining of large parts, coupled with the influence of process techniques and part structure on material flow stability, leads to high residual stress at locations with large velocity gradients, such as the gate and edges of the part. This characteristic is particularly pronounced after painting, resulting in defects such as silver streaks, color differences, deformation, and even cracking.

[0005] The continuous advancement of materials science and technology has provided technical support for the research and development of PC / ABS materials. Through research on modification techniques for polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS), as well as the development and application of novel additives, the performance of PC / ABS materials can be continuously optimized to better meet market and industry demands. For example, Chinese patent CN117887241A discloses a solvent-resistant PC / ABS alloy and its preparation method. This method improves the chemical resistance of the PC alloy by adding highly crystalline polypropylene. However, polycarbonate and polypropylene have poor compatibility. Although maleic anhydride-grafted polypropylene is added for modification, in actual production, especially for larger components such as spoilers and grilles, the risk of phase interface separation leading to delamination on the surface of the component is high in injection molding applications with high injection speeds and shear strength. By improving compatibilizer technology, the interfacial bonding force between PC and ABS can be enhanced, improving the stability and overall performance of the alloy material. For example, Chinese patent CN111040406B discloses a high heat-resistant and chemical-resistant ABS / PC alloy. It utilizes the characteristic that PBT molecular chain segments move quickly and easily migrate to the surface of the part to form a protective layer to improve the chemical resistance of the ABS / PC alloy. However, due to the transesterification and hydrolysis reaction between PBT and PC, the efficiency of the protective layer formed in actual use is low. Therefore, more PBT needs to be added to achieve the desired effect.

[0006] Therefore, for PC / ABS materials used in paintable parts that meet the requirements of lightweight, thin, and high-performance specifications in new energy vehicles, it is necessary to further optimize their molding performance, heat resistance, and paint yield, especially to address defects such as silver streaks and paint cracking. Summary of the Invention

[0007] The purpose of this invention is to address the problems existing in the prior art by providing a PC / ABS material with high paint yield, its preparation method, and its application.

[0008] The objective of this invention can be achieved through the following technical solutions: This invention provides a PC / ABS material with high painting yield, comprising the following components in parts by weight: 40-80 parts of PC resin; 20-30 parts of ABS resin; 5-15 parts of PBT resin; Toughening agent 1-5 parts; 2-10 parts of PBT protective masterbatch.

[0009] Preferably, the PC resin is 45-55 parts; the ABS resin is 25-30 parts; the PBT resin is 5-10 parts; the toughening agent is 4-5 parts; the PBT protective masterbatch is 5-10 parts; the antioxidant is 0.2-0.4 parts; and the lubricant is 0.2-0.3 parts.

[0010] Preferably, the PC resin (polycarbonate) is bisphenol A type polycarbonate. Bisphenol A type polycarbonate includes one or both of phosgene-based and transesterification-based bisphenol A type polycarbonate.

[0011] More preferably, the PC resin is a mixture of polycarbonates produced by different methods, namely, two types of bisphenol A polycarbonates produced by phosgene method and transesterification method. Mixing the two types of polycarbonates in any proportion can obtain a PC alloy with better chemical resistance.

[0012] Preferably, the melt flow rate of the PC resin (at 300℃*1.2kg) is between 10-25 g / min.

[0013] Preferably, the PC resin has a terminal hydroxyl content of 1-10 wt%.

[0014] Preferably, the ABS resin is acrylonitrile-butadiene. A styrene terpolymer, wherein the butadiene rubber content is between 10-20 wt%. The butadiene rubber particle size is between 400-1000 nm.

[0015] Preferably, the intrinsic viscosity of the PBT is 0.5-1.

[0016] More preferably, the PBT is end-capped using SAN-MAH to suppress excessive transesterification between PBT and PC. Preferably, the toughening agent has a silicone / acrylate core and a methyl methacrylate shell, that is, the toughening agent is a methyl methacrylate / silicone / acrylate core-shell type impact modifier.

[0017] More preferably, the toughening agent contains 10 wt% silicone rubber with a rubber particle size of 100-250 nm.

[0018] Preferably, the PBT protective masterbatch contains PC resin, an alcoholysis protectant, and a pH adjuster in a mass ratio of 70-95:3-20:3-10. That is, the PBT protective masterbatch contains 70-95 parts of PC resin, 3-20 parts of alcoholysis protectant, and 3-10 parts of pH adjuster.

[0019] Preferably, the PC resin in the PBT protective masterbatch is a high molecular weight PC resin with a weight-average molecular weight between 30,000 and 40,000 g / mol. The melt flow rate of the PC resin in the PBT protective masterbatch (under 300℃*1.2kg conditions) is between 2 and 7 g / min, preferably 5 to 7 g / min. High molecular weight PC has fewer PC segments and fewer terminal hydroxyl groups, resulting in higher chemical stability and greater resistance to hydrolysis. Using it in masterbatch production can avoid the risk of molecular weight reduction and final product performance degradation after multiple extrusions.

[0020] More preferably, in the PC resin, 50% of the molecular weight distribution ranges within the weight-average molecular weight range of ±2000 g / mol, thereby reducing the molecular weight distribution and avoiding an excessive number of low molecular weight fragments.

[0021] More preferably, the mass ratio of PC resin, alcoholysis protectant, and pH adjuster is 85-95:3-8:3-8.

[0022] More preferably, the mass ratio of PC resin, alcoholysis protectant, and pH adjuster is 85-90:5-8:5-8.

[0023] More preferably, the alcoholysis protectant is a compound containing vinyl and epoxy groups, such as ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA).

[0024] More preferably, the compound containing vinyl and epoxy groups has a neutral pH.

[0025] More preferably, the pH adjuster is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium citrate, sodium gluconate, and sodium dodecylbenzene sulfonate.

[0026] More preferably, the pH adjuster has a pH adjustment capability between 7.0 and 8.0. The adjusting material is in a neutral environment, inhibiting the hydrolysis of PC under acidic or alkaline conditions.

[0027] More preferably, the PBT protective masterbatch is prepared by weighing each component of the masterbatch formula according to the weight ratio, mixing them evenly, and then extruding and granulating.

[0028] More preferably, the extrusion granulation is carried out by a twin-screw extruder for blending and granulation. The extruder speed is 400-700 rpm, the feed section temperature is 220-230℃, the plasticizing section temperature is 240-260℃, the extrusion temperature is 260-280℃, and the pressure is 2-4 MPa. After melt blending, the extruded strip is cooled in a water tank and then granulated to obtain PBT protective masterbatch.

[0029] More preferably, the PBT protective masterbatch also contains 0.3-0.7 parts of processing aids, more preferably 0.3-0.5 parts. The processing aids include one or more of antioxidants, lubricants, and light aging resistant agents.

[0030] Preferably, the PC / ABS material also includes 0.1-0.4 parts of antioxidant and 0.1-0.3 parts of lubricant.

[0031] The antioxidants are polyphenolic antioxidants and phosphate ester antioxidants.

[0032] The phosphate ester antioxidant is a cyclic bisphosphonate. Cyclic bisphosphonates have excellent high-temperature resistance and hydrolysis resistance. The compounding of cyclic bisphosphonate antioxidants can inhibit the occurrence of hindered phenol autocatalytic reactions during the production process, reduce the formation of colored photosensitized quinone structures, prolong the long-term antioxidant performance of the material, and enhance its hydrolysis resistance.

[0033] The lubricant is one or more of the following: silicone powder, pentaerythritol stearate, ethylene bis-stearamide, and oleamide internal lubricant.

[0034] A method for preparing the above-mentioned high-yield PC / ABS material includes the following steps: 1) Weigh each component of the masterbatch formula according to the weight ratio and mix them evenly; 2) The raw materials mixed in step 1) are blended and granulated through a twin-screw extruder. The extruder speed is 400-700 rpm, the feed section temperature is 220-230℃, the plasticizing section temperature is 240-260℃, the extrusion temperature is 260-280℃, and the pressure is 2-4 MPa. After melt blending, the extruded strip is cooled in a water tank and then granulated to obtain PBT protective masterbatch. 3) Weigh each component of the material according to the weight ratio and mix them evenly; 4) The raw materials mixed in step 3) are blended and granulated through a twin-screw extruder. The extruder speed is 400-600 rpm, the feed section temperature is 220-230℃, the plasticizing section temperature is 230-240℃, the extrusion temperature is 240-250℃, and the pressure is 2-4 MPa. After melt blending, the extruded strip is cooled in a water tank and then granulated to obtain the product.

[0035] Preferably, the extruder speed is 400-500 rpm.

[0036] Preferably, before weighing, the PC resin is dried at 100-120℃ for 4-6 hours and then used for later use.

[0037] Preferably, the ABS resin is dried at 90-100℃ for 2-3 hours before weighing.

[0038] Preferably, before weighing, the PBT resin is dried at 100-120℃ for 4-6 hours and then used for later use.

[0039] Preferably, the twin-screw extruder uses an extruder screw with a length-to-diameter ratio of (40-50):1.

[0040] The application of the aforementioned high-yield PC / ABS material in outdoor painted parts. The application is the use of the material in automotive exterior parts.

[0041] Preferably, the material is used in high aspect ratio parts such as automotive spoilers.

[0042] Compared with the prior art, the present invention has the following advantages: (1) The PC / ABS material of the present invention has excellent mechanical properties, heat resistance and chemical resistance. It is dimensionally stable after painting, resistant to paint corrosion and not prone to cracking. It is suitable for automotive exterior parts with high aspect ratio and other painted parts used in outdoor scenarios.

[0043] (2) When the PC / ABS material of the present invention is injection molded, the epoxy group in the alcoholysis protectant containing GMA structure can react with -COOH and -OH, which can seal the terminal hydroxyl groups of PC resin, reduce the number of terminal hydroxyl groups, reduce the transesterification reaction between PBT resin and PC resin, and allow PBT resin to be more dispersed on the surface of the part to form a protective layer resistant to paint corrosion.

[0044] (3) The alcoholysis protectant used in this invention is a compatibilizer containing vinyl groups and epoxy groups, wherein the epoxy groups have high reactivity. The epoxy groups can react with the functional groups on the molecular chains of PC, ABS and PBT, forming chemical bonds at the interface, which improves the compatibility of PC / ABS alloy with PBT. Vinyl groups are flexible, which allows EMA-GMA to be uniformly dispersed between the PC and ABS phases in the PC / ABS blend system, reducing the interfacial tension between the two phases, enabling PC, ABS and PBT to mix more uniformly, reducing phase separation, forming a more stable microstructure, and thus improving the overall performance of the material.

[0045] (4) The pH adjuster used in this invention can control the internal pH of the material in a neutral environment. Under this condition, the polyester is not easy to break the chain due to hydrolysis, which enhances the thermal stability of PC and PBT resin. Enhancing the thermal stability of PC reduces the number of PC molecular chains, thereby reducing the number of terminal hydroxyl groups and avoiding the transesterification reaction of PBT. On the other hand, it reduces the silver streaks on the surface of the parts caused by PC degradation and improves the paint yield.

[0046] (5) In this invention, the alcoholysis protectant and pH adjuster are pre-mixed with PC to form a masterbatch. On the one hand, the alcoholysis protectant reacts with a portion of the PC in advance, reducing the overall activity of the PC resin. On the other hand, the pH adjuster, through the PC resin in the masterbatch, allows for more uniform dispersion in the continuous phase of the alloy, controlling the pH of the alloy environment to be neutral. This promotes the effectiveness of the alcoholysis protectant and pH adjuster and reduces the amount of both used.

[0047] (6) The PC / ABS alloy material of the present invention has low cost, simple production process and high cost performance.

[0048] (7) The masterbatch scheme of alcoholysis protectant and pH adjuster used in this invention can improve the chemical resistance of chemically resistant PC / ABS resins, which are not limited to PBT resin systems. Detailed Implementation

[0049] The embodiments of the present invention will be described in detail below. The following embodiments are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given. However, the protection scope of the present invention is not limited to the following embodiments.

[0050] The raw materials used in the following examples and comparative examples are: PC Resin 1: Idemitsu Kosan Co., Ltd., Japan, IR2600, silicone PC, melt flow rate (300℃*1.2kg): 6g / 10min; PC Resin 2: Covestro AG, PC3208, melt flow rate (300℃*1.2kg): 5g / 10min; PC Resin 3: Nantong Xingchen Synthetic Materials Co., Ltd., PC 105; Melt Flow Rate (300℃*1.2kg): 10g / 10min; PC Resin 4: Nantong Xingchen Synthetic Materials Co., Ltd., PC 10 melt flow rate (300℃*1.2kg): 20g / 10min; ABS resin: Jilin Petrochemical Company, 0215H; PBT resin: DuPont, S600F40; Alcohololysis Protectant 1 (EMA-GMA): Dow Chemical Company, AX8900; Alcohololysis Protectant 2 (EMA): Shanghai Maclean Biochemical Technology Co., Ltd., P922081; Alcohololysis Protectant 3 (GMA): Shanghai Aladdin Biochemical Technology, G106686; Toughening agent: Kanekachi, Japan, PA-40; pH adjuster 1: Sodium citrate from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; pH adjuster 2: Beijing Innocare Technology, sodium dodecylbenzene sulfonate; Hindered phenolic antioxidants: BASF AG, IG-1076; Phosphate ester antioxidants: Ultranox 626, produced by Chemia Corporation; Lubricant: Imoly Oils & Chemicals, P861.

[0051] Before preparing PC / ABS materials, PC resin was dried at 100-120℃ for 4 hours and then used for later use; PBT resin was dried at 100-120℃ for 4 hours and then used for later use; ABS resin was dried at 90-100℃ for 2 hours and then used for later use.

[0052] Preparation of PBT Protective Masterbatch: 1) Weigh PC resin 1, PC resin 2, PC resin 3, alcoholysis protectant, pH adjuster, antioxidant and lubricant according to the weight ratio in Table 1, and mix them evenly; 2) The raw materials mixed in step 1) are blended and granulated by a twin-screw extruder. The extruder speed is 600 rpm, the feed section temperature is 230℃, the plasticizing section temperature is 260℃, the extrusion temperature is 270℃, and the pressure is 4MPa. After melt blending, the extruded strip is cooled in a water tank and then granulated to obtain PBT protective masterbatch 1-4.

[0053] Table 1. Composition of PBT Protective Masterbatch Composition

[0054] Examples 1-7 Preparation of PC / ABS materials with high painting yield: 1) Weigh PC resin 3, PC resin 4, ABS resin, toughening agent, PBT resin, prepared PBT protective masterbatch, alcoholysis protectant, pH adjuster, antioxidant and lubricant according to the weight ratio in Table 2, and mix them evenly. 2) The raw materials mixed in step 1) are blended and granulated through a twin-screw extruder. The extruder speed is 500 rpm, the feed section temperature is 230℃, the plasticizing section temperature is 240℃, the extrusion temperature is 250℃, and the pressure is 3MPa. After melt blending, the extruded strip is cooled in a water tank and then granulated to obtain the product.

[0055] The twin-screw extruder uses an extruder screw with a length-to-diameter ratio of 44:1.

[0056] Table 2 Composition of PC / ABS compositions in the examples

[0057] Comparative Examples 1-10 The preparation method for the comparative example is the same as that for the examples, and the components are shown in Table 3 below. In comparative example 2, an alcoholysis protectant and a pH adjuster are directly added: Table 3. Composition of PC / ABS compositions in comparative examples

[0058] Comparative Example 1 This comparative example is basically the same as Example 2, except that an equal amount of PBT protectant masterbatch 1 is replaced with PBT protectant masterbatch 4.

[0059] Comparative Example 2 This comparative example is basically the same as Example 2, except that PBT protective masterbatch 1 is replaced with an equal amount of PC resin 1, alcoholysis protectant and pH adjuster.

[0060] Comparative Example 3 This comparative example is basically the same as Example 2, except that an equal amount of PBT protectant masterbatch 1 is replaced with PBT protectant masterbatch 2.

[0061] Comparative Example 4 This comparative example is basically the same as Example 2, except that PBT protectant masterbatch 1 is replaced with an equal amount of PBT protectant masterbatch 3.

[0062] Comparative Example 5 This comparative example is basically the same as Example 1, except that the PBT protective masterbatch 1 is replaced with an equal amount of PC resin 3.

[0063] Comparative Example 6 This comparative example is basically the same as Example 2, except that the PBT protective masterbatch 1 is replaced with an equal amount of PC resin 3.

[0064] Comparative Example 7 This comparative example is basically the same as Example 3, except that the PBT protective masterbatch 1 is replaced with an equal amount of PC resin 3.

[0065] Comparative Example 8 This comparative example is basically the same as Example 2, except that PBT protectant masterbatch 1 is replaced with an equal amount of PBT protectant masterbatch 6.

[0066] Comparative Example 9 This comparative example is basically the same as Example 2, except that PBT protectant masterbatch 1 is replaced with an equal amount of PBT protectant masterbatch 7.

[0067] Comparative Example 10 This comparative example is basically the same as Example 2, except that PBT protectant masterbatch 1 is replaced with an equal amount of PBT protectant masterbatch 9.

[0068] Performance testing: The materials obtained from Comparative Examples 1-10 and Examples 1-7 were dried in a forced-air oven at 85°C for 5 hours, and then injection molded into standard specimens and standard blank plates (150mm*100mm*3mm) using a plastic injection molding machine at an injection temperature of 250°C. The injection-molded specimens were immediately placed in a glass desiccator and left at room temperature for at least 24 hours before performance testing. The test results are shown in Table 4.

[0069] (1) Toughness test: Charpy notched impact test was performed using an 80mm*10mm*4mm specimen according to ISO 179 standard, with the unit being kJ / m. 2 .

[0070] (2) Heat resistance test: Vicat softening temperature test was conducted using a 80mm*10mm*4mm specimen according to ISO 306 standard, in °C.

[0071] (3) Chemical resistance test: Use a standard tensile specimen, place it in a 1% strain gauge device, coat the middle of the specimen with 1 mL of Axalta 110892 diluent, let it stand for 24 hours, and evaluate whether there are any changes such as cracking or swelling. If there are, it is judged as NG, otherwise it is OK.

[0072] (4) Paint appearance test: Use a standard bare board for painting. Spray primer 10μm, color paint 18μm, clear varnish 30μm. Level for 10min after each spraying. Place the sample at 80℃ for 30min. After the paint is cured, place the sample in the oven for 72h. Observe whether there are any cracks, marks, bubbles or other changes in appearance. If there are, it is judged as NG, otherwise it is OK.

[0073] Table 4 Properties of PC / ABS Compositions

[0074] The chemical resistance test results of Comparative Examples 5-7 show that the higher the amount of PBT resin added, the better the chemical resistance. However, the notched impact strength test results of Comparative Examples 5-7 show that the higher the amount of PBT resin added, the significantly lower the toughness. This is because PBT resin has lower toughness compared to PC and ABS resins. Furthermore, PBT resin undergoes an ester exchange reaction with PC resin, resulting in molecular chain breakage. Therefore, excessive PBT resin should not be added to PC / ABS alloys to modify chemical resistance. The Vicat softening temperature test results of Comparative Examples 5-7 also show that a higher amount of PBT resin and a lower amount of PC resin leads to a significant decrease in the Vicat softening temperature. For example, Comparative Example 7, despite exhibiting excellent chemical resistance, paint cracking resistance, and blistering resistance, showed deformation due to reduced heat resistance.

[0075] The test results of Example 2 and Comparative Example 1 show that the impact of Example 2 is significantly better than that of Comparative Example 1. The PC resin 3 in the PBT masterbatch 4 used in Comparative Example 1 has high fluidity and is a low molecular weight PC. Therefore, after the masterbatch is made and produced by the extruder, it undergoes severe secondary degradation, with more molecular chain segments, making it easier to undergo transesterification reaction with PBT, resulting in a significant decrease in its toughness, heat resistance and chemical resistance.

[0076] Compared with Comparative Example 2, Example 2 showed better toughness, heat resistance, and chemical resistance. This indicates that the masterbatch method can use less alcoholysis protectant and pH adjuster to achieve better effects in reducing the transesterification reaction between PBT resin and PC resin and improving toughness.

[0077] Compared with Comparative Examples 3 and 4, Example 2 exhibits superior toughness, heat resistance, and chemical resistance. The pH adjuster controls the ambient pH to neutral, making PC less prone to hydrolysis and chain breakage, significantly increasing its thermal stability. It also reduces the number of PC molecular chain segments, thereby reducing the number of terminal hydroxyl groups and preventing PBT from undergoing transesterification. The alcoholysis protectant seals the terminal hydroxyl groups of the PC resin, reducing their number and minimizing transesterification between PBT and PC resins. This allows PBT resin to disperse more extensively on the surface of the part, forming a protective layer resistant to paint corrosion.

[0078] This indicates that the alcoholysis protectant and pH adjuster have a synergistic effect, producing a better effect on reducing the transesterification reaction between PBT resin and PC resin and improving toughness compared to using them alone.

[0079] The addition of alcoholysis protectants and pH adjusters is generally less than 1%, a small amount that leads to uneven dispersion in the PC / ABS system, thus affecting their unstable inhibitory effect on transesterification. In PC / ABS, PC is the continuous phase. Pre-mixing the alcoholysis protectant and pH adjuster with PC to form a masterbatch allows the alcoholysis protectant to react with some of the PC beforehand, reducing the overall activity of the PC resin. Simultaneously, the pH adjuster, through the PC resin in the masterbatch, ensures more uniform dispersion in the continuous phase of the alloy, controlling the pH of the alloy environment at neutral. In summary, using PBT protective masterbatch can promote the effectiveness of alcoholysis protectants and pH adjusters while reducing their usage.

[0080] A comparison of the test results of Examples 2 and 4 shows that their toughness, heat resistance, and chemical resistance are similar, but the toughness of Example 4 is slightly lower than that of Example 2. Silicon in silicon PC exhibits excellent thermal oxidation stability, inhibiting the degradation of PC molecular chains at high temperatures (e.g., reducing ester bond breakage and oxidation reactions). Therefore, the ester bond breakage in silicon PC is less severe than in conventional high-molecular-weight PC, with a further reduction in molecular chain segments, thus further weakening the transesterification reaction between PC and PBT components. Example 2 and Example 5 show comparable performance, and Example 4 and Example 6 show comparable performance, indicating that the addition or absence of antioxidants and lubricants has no effect on the material's chemical resistance and paint resistance.

[0081] Compared to Comparative Examples 8 and 9, Example 2 exhibits superior toughness, heat resistance, and chemical resistance. Alcohololysis protectants containing only epoxy groups result in a decrease in the overall physical properties of the material, while alcohololysis protectants containing only vinyl groups significantly reduce chemical resistance. Only alcohololysis protectants containing both vinyl and epoxy groups can effectively prevent PBT from undergoing transesterification and reduce PC degradation. The synergistic effect of vinyl and epoxy groups maximizes the overall performance of the material.

[0082] Compared with Example 7, Example 2 showed a decrease in notched impact strength, indicating that changing the pH adjuster (within the components specified in this invention) has a certain impact on the overall performance of the material.

[0083] Compared with Comparative Example 10, Example 2 showed better toughness, heat resistance, and chemical resistance. This indicates that the alcoholysis protectant and pH adjuster need to be added in a certain amount to effectively improve the material properties.

[0084] The PC / ABS blend material of this invention exhibits excellent chemical resistance and high paint yield. Through the synergistic effect of alcoholysis protectant and pH adjuster, a sufficient amount of chemically resistant protective layer is formed on the PC / ABS surface using less PBT, thereby achieving paint resistance. Furthermore, the paint-resistant PC / ABS alloy material of this invention has low cost, simple production process, and high cost-effectiveness.

[0085] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A PC / ABS material with high paint yield, characterized in that, The components include the following parts by weight: 40-80 parts of PC resin; 20-30 parts of ABS resin; 5-15 parts of PBT resin; Toughening agent 1-5 parts; 2-10 parts of PBT protective masterbatch; The PBT protective masterbatch contains PC resin, alcoholysis protectant, and pH adjuster in a mass ratio of 70-95:3-20:3-10; The PC resin is bisphenol A type polycarbonate; the melt flow rate of the PC resin under the condition of 300℃*1.2kg is 10-25g / min; The PC resin in the PBT protective masterbatch has a melt flow rate of 2-7 g / min under the condition of 300℃*1.2kg. The alcoholysis protectant is ethylene-methyl acrylate-glycidyl methacrylate.

2. The high-yield PC / ABS material according to claim 1, characterized in that, The ABS resin is an acrylonitrile-butadiene-styrene terpolymer, wherein the butadiene rubber content is 10-20 wt%.

3. The high-yield PC / ABS material according to claim 1, characterized in that, The toughening agent is an impact modifier with a methyl methacrylate / silicone / acrylate core and shell, with silicone / acrylate as the core and methyl methacrylate as the shell.

4. The high-yield PC / ABS material according to claim 1, characterized in that, Preparation of the PBT protective masterbatch: Weigh each component of the masterbatch formula according to the weight ratio, mix them evenly, and then extrude and granulate.

5. The high-yield PC / ABS material according to claim 4, characterized in that, Extrusion granulation is carried out by blending and granulation using a twin-screw extruder with an extruder speed of 400-700 rpm, a feed section temperature of 220-230℃, a plasticizing section temperature of 240-260℃, an extrusion temperature of 260-280℃, and a pressure of 2-4 MPa.

6. The high-yield PC / ABS material according to claim 1, characterized in that, The pH adjuster is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium citrate, sodium gluconate, and sodium dodecylbenzene sulfonate.

7. A method for preparing a PC / ABS material with high paint yield as described in claim 1, comprising the following steps: S1. Weigh each component of the masterbatch formula according to the weight ratio, mix them evenly, and extrude and granulate to obtain PBT protective masterbatch. S2. Weigh each component of the PC / ABS material according to the weight ratio, mix them evenly, and extrude and granulate to obtain the PC / ABS material.

8. The application of a high-yield PC / ABS material as described in claim 1 in painted parts for outdoor use.

Citation Information

Patent Citations

  • A high heat-resistant and chemical-resistant blow-molded ABS / PC alloy material and its preparation method

    CN111040406B

  • Solvent-resistant PC / ABS alloy and preparation method thereof

    CN117887241A

  • PC / ABS alloy with excellent automotive paint crack resistance and preparation method thereof

    CN107118534A

  • PC / ABS composition with favorable oil resistance

    CN107312299A